PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS TERHADAP HARGA SAHAM PROPERTY REAL ESTATE DI BEI - Dewi Ratnawati; Rahman Amrullah Suwaidi (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
This study aims to identify the effect of liquidity ratios, leverage, and profitability on stock prices of property and real estate companies listed on the Indonesia Stock Exchange. The results of the F test obtained the value of Sig. F- Calculate 0.002 < 0.05, which means that the variables Current Ratio (CR) (X1), Debt to Equity Ratio (DER) (X2), and Return On Assets (ROA) (X3) simultaneously affect stock prices. ( Y) Property and Real Estate company listed on the Indonesia Stock Exchange. On the other hand, the t test results show Sig. t-count, Current Ratio (CR) = 0.776> 0.05, Debt to Equity Ratio (DER) = 0.047 <0.05, and Return On Equity (ROE) = 0.003 < 0.05. From the partial calculation, the variable Debt to Equity Ratio (DER)(X2) and Return On Assets (ROA)(X3) have a significant influence on the Stock Price (Y) of the Property and Real Estate Industries listed on the Indonesia Stock Exchange. The Variable Current Ratio (CR) (X1) does not significantly affect the Stock Price (Y) of the Property and Real Estate Industries listed on the Indonesia Stock Exchange.